1969
DOI: 10.1021/ac60274a011
|View full text |Cite
|
Sign up to set email alerts
|

Nonferrous metallurgy. II. Zirconium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, and tungsten

Abstract: HIS REVIEW, as did the previous two Alizarin red S: ceramic materials (387); alkali hydroxides (253); Zr-Ni alloys (692) Pyrocatechol violet: steel (733); HpSO4 solution (787, 799 Zirconin (Gallocyanine MS) : hlg, Al, Ni, Cu (613); Nb, Mo, Fe, Sn, Ti (516) Stilbazogall 11: study of complex (154): Me: (616) study of complex (515); Chromeaxurol S: stidy of cchditions'(302)-' Chloranilic acid: study of conditions (336) Methylthymol blue: study of complex (751) Chlorosulfophenol S: study of conditions (665) p-Chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1970
1970
1977
1977

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 631 publications
(410 reference statements)
0
8
0
Order By: Relevance
“…The effect of ionic strength on the distribution where µ is the ionic strength may be derived from the data of Figure 5. Equation 6is similar to the equation derived by Sides and Kenner (7) for the effect of ionic strength on the distribution coefficients of the alkaline earth metals. The various parameters for the equations representing the data are given in Table III and the experimental and calculated values for log Fmax are shown in Table IV.…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…The effect of ionic strength on the distribution where µ is the ionic strength may be derived from the data of Figure 5. Equation 6is similar to the equation derived by Sides and Kenner (7) for the effect of ionic strength on the distribution coefficients of the alkaline earth metals. The various parameters for the equations representing the data are given in Table III and the experimental and calculated values for log Fmax are shown in Table IV.…”
Section: Resultsmentioning
confidence: 70%
“…Chem., 38, 707 (1966). and Kenner (7) confirmed this result but found that the distribution coefficients for these ions again increased in the region of pH 7 and above. They also showed that an increase in ionic strength caused a decrease in the coefficients.…”
mentioning
confidence: 73%
See 3 more Smart Citations